Arturo Cerdá y Rico’s photography as a landscape interpretation and enhancement tool - Fernández-Portela, Julio; López-Rodríguez, Ramón (Revista de Estudios Andaluces, 2021)
Environmental, social and cultural processes affect the landscape and change over time. To a large extent, safeguarding its values depends on our knowledge of them, and an in-depth study of their evolution calls into play natural and cultural, material and immaterial, tangible and intangible factors. This project’s objectives are two-fold: firstly, to put Cerdá y Rico’s photography in the spotlight and, secondly, to design a sightseeing tour through the town of Cabra del Santo Cristo (Jaén). Historical photography serves the dual purpose of studying the landscape and highlighting a geographical area’s resources, which is why Arturo Cerdá y Rico’s photographic legacy is fundamental, and the pictures and fieldwork will be used to identify and geo-reference this route’s main landmarks with the Wikiloc tool.The result is the design of a 5.5 km route divided into ten sections with more than 45 milestones that include the region’s existing heritage resources.